The Plain Inquirer’s Plain Evidence against the Global Skeptical Scenarios - Leite, Adam (International journal for the study of skepticism, 2018)
Penelope Maddy claims that we can have no evidence that we are not being globally deceived by an evil demon. However, Maddy’s Plain Inquirer holds that she has good evidence for a wide variety of claims about the world and her relation to it. She rejects the broadly Cartesian idea that she can’t be entitled to these claims, or have good evidence for them, or know them, unless she can provide a defense of them that starts from nowhere. She likewise rejects the more limited demand for a defense that makes use only of considerations that do not concern the world outside of her mind. She allows that some considerations about the world can be appealed to perfectly appropriately as fully adequate evidence in favor of other considerations about the world. So why can’t the Plain Inquirer rule out global skeptical hypotheses by producing evidence against them that depends upon other considerations about the world? Is there good reason for singling out global skeptical hypotheses such as I am not being deceived by an evil demon as requiring a different kind of treatment? Considerations about epistemic asymmetry and epistemic circularity, as well as Wittgensteinian considerations about the relation between evidence and the real-world and human background context, all lead to the conclusion that there is not.